Study on the anaphylactoid of three phenolic acids in Honeysuckle. (21st July 2015) - Wang, Fang; Li, Cunyu; Zheng, Yunfeng; Li, Yu; Peng, Guoping
Abstract: Ethnopharmacological relevance: Chlorogenic acid (CA) is one of the major ingredients in Honeysuckle which exhibits anticancer, antibacterial, antiviral, hypoglycemic and anti-HIV activities. However, with the frequent emergence of anaphylactoid reactions of traditional Chinese medicine (TCM) injections which contains Honeysuckle in recent years, many researchers found that CA exhibited allergenicity. Aim of the study: To explore the changes of content of CA, neochlorogenic acid (NCA) and cryptochlorogenic acid (CCA) during the preparation of Honeysuckle and evaluate the anaphylactoid of these three ingredients. Materials and methods: Two extracts of Honeysuckle were prepared by different methods and the content of CA, NCA and CCA were determined by high performance liquid chromatography (HPLC) analysis. Guinea pig and mast cells RBL-2H3 were utilized as the animal and cell model to investigate the anaphylactoid of these three ingredients. Results: The content of CA decreased while CCA and NCA increased during the preparation of Honeysuckle. In vitro and in vivo studies showed that CA and CCA could significantly increase the plasma serotonin and β-hexosaminidase levels in guinea pigs and induce the degranulation of RBL-2H3 cell, while NCA did not show such properties. In addition, CAA had a stronger effect than CA. Conclusion: We believed that both CA and CCA could cause anaphylactoid reaction while NCA could not. Moreover, the anaphylactoid of CCA is higher than CA. Our result demonstrated that CA is not the only cause of anaphylactoid reactions of TCM injections which contains Honeysuckle. Graphical abstract: